Effects of Dietary Protein and Lipid Levels with Different Protein‐to‐Energy Ratios on Growth, Feed Utilization, and Plasma Biochemical Parameters of Dianchi Golden‐line Barbell, Sinocyclocheilus grahami. Issue 5 (21st November 2017) - Wang, Zhen; Wang, Kun; Deng, Junming; Zhang, Lu; Mi, Haifeng; Chen, Xiaolu
Abstract: An 8‐wk feeding trial was conducted to evaluate the effects of varying dietary protein and lipid levels with different protein‐to‐energy (P/E) ratios on growth, feed utilization, and plasma biochemical parameters of Sinocyclocheilus graham . Nine experimental diets were formulated to contain three protein levels (35, 40, and 45%), and each with three lipid levels (4, 8, and 12%), to produce a range of P/E ratios from 71.31 to 98.64 mg protein/kcal. Each diet was randomly assigned to triplicate groups of 25 fish. Fish grew best when fed the diet containing 45% protein and 12% lipid. However, fish fed the diet with 40% protein and 8% lipid had similar weight gain and specific growth rate as those fed the above diet but showed relatively better feed conversion ratio, protein efficiency ratio, and protein and energy retentions. Additionally, plasma total amino acids and blood urea nitrogen contents and γ‐glutamyltransferase, aspartate aminotransferase, and alanine aminotransferase activities in fish fed the diet containing 40% protein and 8% lipid were relatively low among the dietary treatments. These results may indicate that a diet containing 40% protein and 8% lipid with P/E ratio of 84.05 mg protein/kcal would be suitable for the optimal growth, feed utilization, and health of S. graham .